Variasi kemasan Lontar, persepsi kemasan berkelanjutan, dan minat pembelian: Peran mediasi harga dalam pengambilan keputusan konsumen - Amaral, Maria Augustin Lopes; Klau, Anggelina Delviana; Ketmoen, Adrianus; Bau Mau, Ignatia Thomasita; Taninhelon, Defita Desideria (Journal of Management and Digital Business, 2024)
This study explores the interplay between packaging variety, perception of sustainable packaging, price, and consumer purchase intention regarding lontar packaging. Utilizing a quantitative approach, data were gathered from an online survey of 153 environmentally conscious consumers in Kupang City, selected through convenience sampling. The analysis employed Structural Equation Modeling—Partial Least Squares (SEM-PLS). Key findings reveal that the perception of sustainable packaging significantly influences consumer purchase intention. Conversely, while packaging variety does not directly affect purchase intention, it impacts product pricing. Price is a mediator in the relationship between packaging variety and purchase intention. However, the perception of sustainable packaging does not mediate this relationship. The managerial implications emphasize the need for integrating sustainability perceptions into packaging design and developing pricing strategies that align with consumer preferences. Additionally, effective marketing strategies should leverage the mediating role of price to enhance product appeal. This research contributes to understanding market dynamics related to packaging and consumer behavior, particularly in the context of sustainability.